The Neotropical genus Eudexia Brauer & Bergenstamm, 1889 (Tachinidae: Dexiinae: Dexiini): lectotype fixation for the type species, synonymy, and a new species from Brazil - de Santis, Marcelo Domingos (Zootaxa, 2021)
Eudexia Brauer & Bergenstamm, 1889, a Dexiini genus restricted to the Neotropical Region, is revised with proposal of the following new synonymies: Chaetocalirrhoe Townsend, 1935 = Eudexia, syn. nov. and Cordillerodexia Townsend, 1927 = Eudexia, syn. nov. As a result, the following new combinations are proposed: Eudexia brevicornis (Macquart, 1851), comb. nov., Eudexia colombiana (Townsend, 1929), comb. nov., Eudexia grandis (Townsend, 1935), comb. nov., and Eudexia orientalis (Townsend, 1927), comb. nov. Redescriptions, photographs and a lectotype designation are provided for the type species Eudexia formidabilis (Bigot, 1889). Diagnoses and photographs are provided for Eudexia colombiana, E. grandis, and E. orientalis, and a diagnosis is provided for E. brevicornis. A new species from Brazil, Eudexia lopesi sp. nov., is described. Finally, an updated diagnosis for the genus Eudexia and a key to the seven known species are given.